2018
DOI: 10.20869/auditf/2018/149/122
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of employees’ psychological ownership on budgetary slack

Abstract: The existence of budgetary slack permeates every level of private sector organisations. Employees (i.e., budget makers) usually request excessive budgetary resources in the budgeting process. Due to its dysfunctional nature, existing researchers had extensively examined the relationship between budgetary slack and employees' performance. This study adopted a survey questionnaire approach to examine the relationship between determinants of psychological ownership and employees' intention to create slack in budg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Therefore, personal characteristics have a stronger influence in the cultivation of extra-role behavior (OCB) than attitude (Yee et al, 2018). It also confirms that PO's direct effects in creating OCB are stronger with JS.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Therefore, personal characteristics have a stronger influence in the cultivation of extra-role behavior (OCB) than attitude (Yee et al, 2018). It also confirms that PO's direct effects in creating OCB are stronger with JS.…”
Section: Discussionmentioning
confidence: 63%
“…The findings of this study suggest that such personal characteristics (Yee et al, 2018) have a greater impact on attitudes toward extra-role behaviour (OCB). The study results also indicate that PO significantly affects OCB.…”
Section: Conclusion and Limitationsmentioning
confidence: 77%
See 2 more Smart Citations
“…Many previous studies have demonstrated that the manager's participation resulted in budgetary slack. Most of them, by utilizing agency theory (Baiman et al, 2000;Namazi, 1985) and psychological paradigms (Andre et al, 2016;Cheok et al, 2018;Hartmann and Maas, 2010;Young et al, 2021) have been focused on the manager's participation in budgeting and its effect on the use of budgetary slack (Macinati and Rizzo, 2014;Maiga and Jacobs, 2007;Merchant, 1985).…”
Section: Introductionmentioning
confidence: 99%